Leadership capacity for lasting school improvement - Lambert, Linda, 1939- (Association for Supervision and Curriculum Development, 2003)
Following the publication of Building Leadership Capacity in Schools in 1998, Linda Lambert visited educators around the world to see how they had applied the ideas presented in her book to their schools and districts. Though everyone she spoke with agreed on the importance of high leadership capacity, they also had many questions about how best to achieve this goal. Leadership Capacity for Lasting School Improvement is the author's attempt to answer those questions. The book begins by outlining the five major prerequisites for high leadership capacity: . Skillful participation in the work of leadership . Inquiry-based use of data to inform decisions and practice . Broad involvement and collective responsibility for student learning . Reflective practice that leads to innovation . High or steadily improving student achievement In addition to providing a comprehensive overview of steps schools should take to meet these criteria, the author quotes at length from her discussions with educators to provide a view of leadership enhancement techniques in practice. Finally, the handy rubrics and surveys at the end of the book can be used by teachers and administrators alike to personally assess their leadership skills. By combining the author's own insights with real-life examples and practical exercises, Leadership Capacity for Lasting School Improvement offers invaluable guidance to educators at all stages of development. Linda Lambert is founder of the Center for Educational Leadership at California State University, Hayward, where she is professor emeritus. She is coauthor of The Constructivist Leader (1995) and Who Will Save Our Schools: Teachers as Constructivist Leaders (1997) and author of Building Leadership Capacity in Schools (1998).